2018
DOI: 10.7577/seminar.2597
|View full text |Cite
|
Sign up to set email alerts
|

How to trigger students’ interest in digital learning environments: A systematic literature review

Abstract: The digital revolution and globalization have a deep influence on education at all levels. Various digital devices do not only provide students’ Internet connections, but also create more opportunities for them to get inspired, motivated, and engaged in learning activities. Recent research shows that triggering interest can enhance students’ self-regulation, collaboration, problem-solving, and joy of learning. Previous studies show that the pedagogical use of information and communication technology (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Teachers’ perspectives on using InVID-WeVerify highlight how implementation is possible and may trigger interest among students (Sun et al 2018 ). Nevertheless, teachers and students seem to need hard and soft scaffolds and updated heuristics to be able to use such artefacts in constructive ways, as also noted in previous research (Nygren and Vikström 2013 ; Nygren et al 2014 ; Saye and Brush 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers’ perspectives on using InVID-WeVerify highlight how implementation is possible and may trigger interest among students (Sun et al 2018 ). Nevertheless, teachers and students seem to need hard and soft scaffolds and updated heuristics to be able to use such artefacts in constructive ways, as also noted in previous research (Nygren and Vikström 2013 ; Nygren et al 2014 ; Saye and Brush 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitäten, die durch interaktive Lehr- und Lernmodelle entstehen können, sind etwa eine Steigerung des Interesses an den gelehrten Inhalten, die Förderung des Austauschs zwischen Lehrenden und Studierenden sowie eine erhöhte Motivation und Zufriedenheit der Interaktionspartner*innen (Sun et al. 2018 , S. 77 f.). Kritisch wird das Modell der ressourcenoptimierten Universität allerdings insofern gesehen, als mitunter bezweifelt wird, dass sich mit aufgezeichneten Vorlesungen tatsächlich nennenswert Ressourcen einsparen ließen.…”
Section: Zukunftsszenarienunclassified
“…Dörnyei (2020) suggested that teachers should actively keep students engaged and not just focus on the subject content. Sun, Siklander, and Ruokamo (2018) identified, in a literature review, factors that trigger and stimulate learning in digital environments. According to their results, visible in Figure 2.…”
Section: Figurementioning
confidence: 99%